Post-Biblical history of the Jews: from the close of the Old Testament, about the year 420 B. C. E., till the destruction of the second temple in the year 70 C. E - Raphall, Morris J. (Moss & Brother, 1855)
Bk. 1. Judea under the Persians and Greeks -- bk. 2. The Maccabees -- bk. 3. The Asmoneans -- bk. 4. The Romans in Judea.